Government’s Role in Creating a Start-Up Ecosystem : The Indian Youth's Perception - Khatik, S. K.; Shrivastava, Geetanjali (Prabandhan: Indian Journal of Management, 2023)
Purpose : The purpose of this research was to investigate the perception of Indian youth regarding the start-up environment in India. The study aimed to identify the factors influencing the youth’s perception and determine their attitudes toward entrepreneurship in the Indian scenario. Methodology : The study analyzed the relationship between the constructs using a descriptive research technique. This study’s data was acquired using a standardized questionnaire and verified metrics. The data were acquired mostly from the Bhopal city by using a Google form (Madhya Pradesh). The inverse square root method was used to compute the sample size required for the study. Using SmartPLS software, the structural model of the study was examined, and the hypotheses were tested. Findings : According to the study’s findings, government initiatives are the most influential factor in creating an environment for start-ups. The start-up ecosystem has the most direct impact on promoting start-ups. Practical Implications : The government’s policies and initiatives play a crucial role in promoting entrepreneurship and creating an environment that supports start-up growth. Government support programs can help young entrepreneurs access funding, mentorship, and other resources necessary to start and grow a successful business. Originality : Previous research on start-ups has often focused on factors such as access to capital, market conditions, and regulatory environments. However, understanding the perceptions of Indian youth towards the government’s role in creating a start-up ecosystem can provide a unique perspective on how the government can effectively support start-ups in India.